A comparative of cologe physical education study between the individual games in teaching communication skills education in accordance with years of experience - moufed , raea (Journal of Physical Education, 2011)
The research aims to identify the differences between the teaching of individual games in the Faculty of Physical Education - University of Baghdad in communication skills education in accordance with years of experience. The research sample consisted of individual games and the teaching of number (94) teaching at a rate of 46.3%. After taking note of the research and similar studies the researcher designed a questionnaire, which included the form on the areas of communication skills education, and having extracted these areas after the presentation to the experts, which has been modified fields from nine to seven areas, where the merged areas (6.7, 8) within a single domain which is (the skills of the signals non-verbal / silent, isotopes of language), have revealed a researcher on the efficiency and the ability of the form through the analysis of the paragraphs of each form, after completion of the experiment the main researcher for data collection, arranged in two groups according to experience for more than ten years and less than ten years and conducted the appropriate statistical treatments. Where the results indicated the emergence of Mad statistically significant differences between the individual games in teaching communication skills education in accordance with years of experience for less and more than ten years. The researcher recommends the need for the attention of faculty teaching communication skills because of its positive significance in the educational process .